Integration of Heroic Values and Banjar Culture in Islamic Education to Shape National Character - Hary Nurdi; Zulfa Jamalie (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to analyze the integration of heroic values and Banjar culture in Islamic education as an effort to shape a religious, nationalistic, independent, and noble national character. This study employs a library research method using a descriptive qualitative approach. The data sources were obtained from various literature materials, including books, scientific journals, academic articles, Banjar cultural documents, and references related to Islamic education and character education. The data analysis techniques were carried out through data reduction, classification, interpretation, and systematic conclusion drawing. The findings reveal that the heroic values embedded within Banjar society, such as courage, responsibility, social solidarity, religiosity, hard work, and the spirit of dedication, have strong relevance to the objectives of Islamic education in forming insan kamil (the complete human being). Banjar culture also contains local values that support the formation of national character, including mutual cooperation, deliberation, politeness, respect for religious scholars, and religious traditions rich in moral education. The integration of these values into Islamic education can be implemented through curriculum development, local culture-based learning, teacher exemplification, religious habituation, and social community activities. The novelty of this study lies in its effort to connect the heroic values of Banjar society with the concept of character education in Islamic education in an integrative and contextual manner as a model for strengthening national character based on local wisdom